ICTs and Mainstreaming Gender - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
by Nancy Hafkin & Helen Hambly Is it realistic to expect ICTs to be relevant to the world´s 876 million illiterate people, two-thirds of whom are women living in rural areas of developing countries? Women make up the largest propo